On the applicability of the synergetic approach in political research - E. N. Maksimova (Современная наука и инновации)
The article summarizes some provisions of synergetics and assesses the possibility of their application to the objects of political science. The author suggests that the synergetic approach is applicable to the study of political processes and dynamic states of political systems. The features of political systems from the point of view of synergetics are clarified: a combination of organizational and self-organizational principles; openness and dynamism; nonlinearity and multilevelness. The conclusion is made about the applicability of the synergetic approach in studies of stable and unstable states of political systems, as well as about the prospects of using adapted provisions of synergetics in explaining crisis phenomena and transitional processes in politics.